Penggunaan Model Binomial Pada Penentuan Harga Opsi Saham Karyawan - Anggraeni, Dara Puspita (Jurnal Matematika, 2015)
Binomial Model for Valuing Employee Stock Options. Employee Stock Options (ESO) differ from standard exchange-traded options. The three main differences in a valuation model for employee stock options : Vesting Period, Exit Rate and Non-Transferability. In this thesis, the model for valuing employee stock options discussed. This model are implement with a generalized binomial model.
Keywords: Employee Stock Options; Vesting Period; Exit Rate; Binomial Model